Gingerol-Enriched Ginger Supplementation Mitigates Neuropathic Pain via Mitigating Intestinal Permeability and Neuroinflammation: Gut-Brain Connection - Shen, Chwan-Li; Wang, Rui; Yakhnitsa, Vadim; Santos, Julianna Maria; Watson, Carina; Kiritoshi, Takaki; Ji, Guangchen; Hamood, Abdul Naji; Neugebauer, Volker (Frontiers in Pharmacology, 2022)
Objectives: Emerging evidence suggests an important role of the gut-brain axis in the development of neuropathic pain (NP). We investigated the effects of gingerol-enriched ginger (GEG) on pain behaviors, as well as mRNA expressions of inflammation via tight junction proteins in GI tissues (colon) and brain tissues (amygdala, both left and right) in animals with NP. Methods: Seventeen male rats were randomly divided into three groups: Sham, spinal nerve ligation (SNL, pain model), and SNL+0.375% GEG (wt/wt in diet) for 4 weeks. Mechanosensitivity was assessed by von Frey filament tests and hindpaw compression tests. Emotional responsiveness was measured from evoked audible and ultrasonic vocalizations. Ongoing spontaneous pain was measured in rodent grimace tests. Intestinal permeability was assessed by the lactulose/D-mannitol ratio in urine. The mRNA expression levels of neuroinflammation (NF-κB, TNF-α) and tight junction proteins (Claudin-1, Claudin-3, Zonulin, and Occludin) in the colon and amygdala (right and left) were determined by qRT-PCR. Data was analyzed statistically. Results: Compared to the sham group, the SNL group had significantly greater mechanosensitivity (von Frey and compression tests), emotional responsiveness (audible and ultrasonic vocalizations to innocuous and noxious mechanical stimuli), and spontaneous pain (rodent grimace tests). GEG supplementation significantly reduced mechanosensitivity, emotional responses, and spontaneous pain measures in SNL rats. GEG supplementation also tended to decrease SNL-induced intestinal permeability markers. SNL increased the mRNA expression of Claudin-3 and Zonulin in the amygdala, as well as Claudin-1 and Occludin in the colon, while GEG supplementation decreased SNL-induced Claudin-3 and Zonulin mRNA expression in the left amygdala and Claudin-1 and Occludin mRNA expression in the colon. The SNL group had increased mRNA expression of NF-κB and TNF-α in the right amygdala and colon; GEG supplementation mitigated these changes in SNL-treated rats. Conclusions: This study suggests GEG supplementation palliated a variety of pain spectrum behaviors in a preclinical NP animal model. GEG also decreased SNL-induced neuroinflammation, intestinal permeability, and potentially the breakdown of the blood-brain barrier, which may explain the behavioral effects of GEG.